Determination of normal testicular development in tropical adapted South African Beef Bulls during phase C (centralised testing centre) - Mampuru, Sophia Makopi (My University, 2023)
Bull fertility is considered the most important consideration in the herd because bulls are responsible for conception across several females. There is a high correlation between scrotal circumference and fertility in bulls, and the bigger the better. However, there is a lack of information on the normal testicular development in tropical adapted beef bulls in South African. Therefore, a study was conducted to determine the normal testicular development by age and breed in tropical adapted South African beef bulls enrolled with the INTERGIS during Phase C testing. The recorded data was sourced from the ARC and analysed using the International Business Machines (IBM) Statistical Package for the Social Sciences (SPSS), version 25. The study used thirteen beef breeds namely; Angus SA, Afrikaner, Beefmaster, Bonsmara, Brahman, Charolais, Drakensberger, Hereford, Nguni, Limousin, Santa Gertrudis, Simmental, and Sussex. The bulls were between the ages of 150 and 250 days when admitted to Phase C with a testing length of 270 days. Analysis of variance (ANOVA) and Pearson’s correlation were used for data analysis. ANOVA results indicated that the Simmental bulls had the highest SC (36.00 cm) while the Brahman bulls had the lowest SC (30.00 cm). The results also showed a significant difference (P<0.05) between breeds on SC with the exception of the Sussex, Brahman, Santa Gertrudis, Hereford and the Nguni. The results for Pearson’s correlation showed a highly significant correlation (P<0.01) on the breed and SC for all the breed with the exception of the Simmental and the Hereford. The breed and age of tropically adapted beef bulls had an effect on their SC. There was a significant difference between different age groups (P<0.01) with the exception in Nguni, Sussex and Brahman (P>0.05) cattle breeds.
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2023
Keywords: Scrotal circumference; Age; Breeds; Testicular development; South African Beef Bulls; Bull fertility; INTERGIS; Scrotum; Beef cattle breeds; Cattle -- Age determination; Cattle -- Aging; Cattle -- Breeding -- South Africa; Cattle -- Fertility